Repair of deep deltoid ligament ruptures near the medial malleolar attachment or midsubstance rupture by using suture anchors into the talus combined with the transosseous suture in the medial malleolar - Liang, Wei; Zhou, Mingping; Jiang, Zhongting; Mao, Xuanyu; Zhou, Xiang; Wang, Fei (Frontiers in Surgery, 2024)
Purpose: For deep deltoid ligament ruptures near the medial malleolar attachment, anchors were usually placed at the posterior colliculus and intercollicular groove. However, this procedure usually requires a prolonged surgical incision to fully expose the deep deltoid ligament, causing more trauma. In order to reduce surgical trauma, we explored the treatment outcomes of suture anchor into the talus combined with transosseous suture in the medial malleolar for the treatment of deep deltoid ligament ruptures near the medial malleolar attachment or midsubstance rupture. Patients and Methods: This is a retrospective study of patients who received suture anchor into the talus combined with transosseous suture in the medial malleolar for repairing deltoid ligament ruptures near the medial malleolar attachment or midsubstance rupture. The outcome measures include the American Orthopaedic Foot and Ankle Society (AOFAS) ankle-hindfoot score, visual analogue scale (VAS), and the active range of motion (ROM) of the ankle at the final follow‑up visit after surgery. Medial malleolus gap was evaluated by radiographic examination. Results: This study included 64 patients. The mean follow-up time was 36.3 ± 15.2 months. There were 43 patients with injuries on the medial malleolar side, and 21 cases on the midsubstance. The average AOFAS and VAS were 87.5 ± 4.9 and 0.7 ± 0.5, respectively. No significance in medial malleolus gap between the contralateral side and affected side was observed. Conclusion: For deltoid ligament ruptures near the medial malleolar attachment or midsubstance rupture, suture anchor into the talus combined with transosseous suture in the medial malleolar yields good clinical effect and outcome, is an optimal management of ankle syndesmosis injuries